1999
DOI: 10.1007/s004670050701
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular abnormalities in Bardet-Biedl syndrome

Abstract: Bardet-Biedl syndrome (BBS) is a rare autosomal recessive disorder. Specific diagnostic criteria for BBS have now been defined. At least four of the five cardinal signs of mental retardation, obesity, hypogenitalism in men, distal limb anomalies, and progressive tapetoretinal degeneration of the retina are required for the diagnosis. Renal involvement has been described as a sixth cardinal feature. Chronic renal failure occurs in 30%-60% of patients. Hypertension has been noted in 50%-66% of cases. Renal abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
12
0
5
Order By: Relevance
“…In other studies, fetal lobulation and non‐communicating calyceal cysts or diverticula or clubbing have been found as characteristic renal findings (occurring in 70–96% of patients) [12,81], whereas 20% had diffuse and 4% focal cortical loss [12]. A recent study has reported a BBS patient with bilateral microaneurysms and occlusion in renal arterioles [74]. The most common and earliest functional abnormalities are polydypso‐polyuria and reduced ability to concentrate (which may lead to some difficulties, especially in infancy) and an end‐stage renal disease can develop [7,11,12,82,83], with the requirement for haemodialysis maintenance [7] or renal transplantation, also in childhood [83].…”
Section: Literature Review and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In other studies, fetal lobulation and non‐communicating calyceal cysts or diverticula or clubbing have been found as characteristic renal findings (occurring in 70–96% of patients) [12,81], whereas 20% had diffuse and 4% focal cortical loss [12]. A recent study has reported a BBS patient with bilateral microaneurysms and occlusion in renal arterioles [74]. The most common and earliest functional abnormalities are polydypso‐polyuria and reduced ability to concentrate (which may lead to some difficulties, especially in infancy) and an end‐stage renal disease can develop [7,11,12,82,83], with the requirement for haemodialysis maintenance [7] or renal transplantation, also in childhood [83].…”
Section: Literature Review and Discussionmentioning
confidence: 85%
“…Renal disease must certainly be considered a cardinal feature of BBS [50,74–78]. Chronic renal failure occurs in 30–60% of patients and hypertension has been noted in 50–60% of cases [74]. Renal abnormalities reflect a defect in maturation of the kidneys [74].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, some microaneurysms are sclerosed and non-perfused while others can be observed as fully or partially perfused during fluorescein angiography (Kohner and Dollery, 1970;Kohner and Henkind, 1970). Microaneurysms do not occur in diabetic rodents and therefore histological studies have been limited although it is apparent that hypertension, endothelial proliferation, thrombus formation and pericyte cell-death are causal or contributory factors to their formation (Amemiya and Bhutto, 2001;Baskin et al, 1999;Ishikawa et al, 1983;Stitt et al, 1995;Tolentino et al, 1996) (Figure 9). On retinal trypsin digest preparations of post-mortem human eyes, microaneurysms occur largely on the arteriolar side of the circulation upstream of denuded arterioles and in association with large areas of capillary acellularity (Gardiner et al, 2007).…”
mentioning
confidence: 99%
“…Bardet-Biedl sendromunda hipertansiyon sıklığı %50-66 arasında bildirilmektedir. Hipertansiyonun nedeni net olarak ortaya konamamış olmakla birlikte; direkt olarak mutant genin etkisi, vasküler anomaliler, renal parankimal hastalık ya da obeziteyle ilişkili olabileceği öne sürülmektedir [2,10]. O'Dea ve arkadaşlarının yaptığı çalışmada, Bardet-Biedl sendromlu hastaların %25'inde kronik böbrek hastalığı tespit edilirken, mortalite görülen olgularda bu oranın %75'e çıktığı bildirilmiştir [2].…”
Section: Discussionunclassified